Female Staff Sexual Misconduct: The Importance of Understanding and Acting on the Data. (June 2015) - Moss, Andie
This commentary looks at the recent findings of Allen Beck, PhD, on the subject of staff sexual misconduct in the field of corrections. This commentary aims to explore the importance of cultivating an in-depth understanding of the unique nature of female staff sexual misconduct and the cause and effect of policy and operational best practices implementation to ensure a sexually safe environment for both facility and agency leadership and inmates.